Pengelolaan sampah berbasis masyarakat di era new normal (Pendampingan pengelolaan bank sampah Puri Berlian Kelurahan Air Putih di era normal) - Titi Antin; Darusman Darusman; Yefni Yefni (Unri Conference Series: Community Engagement, 2020)
Puri Berlian waste bank is located in RT.04/RW.02 of Air Putih Village, Tampan District. Based on the FGD result (focus group discussion) with the waste bank management, several issues can be identified, namely: waste bank is inactive during the Covid-19 Pandemic that causes the piling of the customers wastes; lack of literacy regarding waste, most of the customers have yet to understand the impacts caused by waste as well as the management of waste banks. The goal to be achieved is re-activating the activity of the waste bank during this new normal era while providing the general knowledge about waste towards the members. The methods used for this study are giving socialization and education regarding the benefit of waste banks, supporting the reactivation of waste bank activities, and formulating the development plan for the waste bank. The results of this study show that the activity of waste storing is recommenced gradually, local people who have not become the member are persuaded to be the customer, and the development of a bank subunit of used cooking oil (minyak jelantah) is explored.